2020
DOI: 10.1558/isla.40636
|View full text |Cite
|
Sign up to set email alerts
|

A self-paced reading study of language processing and retention comparing guided induction and deductive instruction

Abstract: The present study measured the effects of guided-inductive (GI) versus deductive computer-delivered instruction on the processing and retention of the Spanish true passive using a self-paced reading design. Fifty-four foreign language learners of Spanish participated in the study, which operationalised guided-inductive and deductive approaches using an adaptation of the PACE model and processing instruction (PI), respectively. Results revealed that each experimental group significantly improved after the pedag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…It is also important to note that these studies have used a variety of methodological approaches. For example, many studies employ eye-tracking (e.g., Issa & Morgan-Short, 2019;Ito & Wong, 2019;Wong & Ito, 2018), but some use SPR (Dracos & Henry, 2021;Malovrh et al, 2020;McManus & Marsden, 2017). Further, some studies measure online processing during the training task itself (e.g., Benati, 2020c;Issa et al, 2015;Wong & Ito, 2018), meaning that reported changes in processing could be related directly to either the task itself or the provision of feedback during these tasks (or both).…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
“…It is also important to note that these studies have used a variety of methodological approaches. For example, many studies employ eye-tracking (e.g., Issa & Morgan-Short, 2019;Ito & Wong, 2019;Wong & Ito, 2018), but some use SPR (Dracos & Henry, 2021;Malovrh et al, 2020;McManus & Marsden, 2017). Further, some studies measure online processing during the training task itself (e.g., Benati, 2020c;Issa et al, 2015;Wong & Ito, 2018), meaning that reported changes in processing could be related directly to either the task itself or the provision of feedback during these tasks (or both).…”
Section: Interpreting the Effects Of Pimentioning
confidence: 99%
“…(2016) demonstrated the effectiveness of video games on learning outcomes. Previous research has demonstrated the effectiveness of sentence–picture matching tasks on learning outcomes (Lee et al., 2020; Malovrh et al., 2020). These studies also show that learning takes place in groups as well as in individual (isolated) settings.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of the information structure we analyzed was how much information the rule included or the rule's completeness. Previous quantitative research has linked longer processing times with greater DoP during GI instruction (Adrada–Rafael, 2017; Malovrh et al., 2020) and deductive instruction (Lee & Doherty, 2019a; Lee et al., 2020). The results of the present qualitative study suggest a possible link between longer processing times and DoP as reflected by rule completeness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations